2022
DOI: 10.1038/s41598-022-17975-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vegetation spatial pattern on erosion and sediment particle sorting in the loess convex hillslope

Abstract: To address the problem of serious soil erosion on the Loess Plateau, under the conditions of limited vegetation measures, the runoff erosion characteristics and erosion sediment sorting characteristics of vegetation at different positions on the upper slope of convex hillslopes are investigated, and the optimal vegetation spatial pattern is proposed according to the benefits of water storage and sediment reduction at different vegetation positions. The fluctuation degree of flow discharge per unit area of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Pattern D exhibits the largest reductions in runoff and sediment. This result is consistent with the reports of Su et al (2022) and Bai et al (2022) based on which vegetation planted on a slope effectively reduces the runoff and sediment.…”
Section: Discussionsupporting
confidence: 93%
“…Pattern D exhibits the largest reductions in runoff and sediment. This result is consistent with the reports of Su et al (2022) and Bai et al (2022) based on which vegetation planted on a slope effectively reduces the runoff and sediment.…”
Section: Discussionsupporting
confidence: 93%
“…During water erosion, splashing raindrops and runoff scouring are the main energy sources (Su et al, 2022). Vegetation intercepts rainfall through the canopy, thereby reducing the energy of the raindrops (Kervroëdan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Four main mechanisms underlying the control of soil and water loss by vegetation restoration have been suggested: (1) vegetation mechanically intercepts rainfall through its multi‐level aboveground parts (i.e., forest canopy), which reduces the energy of splashing raindrops and runoff yield (Kervroëdan et al, 2021); (2) vegetation reduces runoff yields because litter absorbs some water and the soil water infiltration capacity is increased (Han et al, 2021; Zhou et al, 2016); (3) vegetation roughens the slope surface, increases the flow resistance, and reduces the flow velocity (Zhang et al, 2018); and (4) vegetation roots promote soil aggregate formation, which improves the soil stability and reduces sediment loss (Hou et al, 2020). The pattern of the vegetation is important for the control of runoff and sediment yields (Bartley et al, 2006; Bautista et al, 2007; Shi et al, 2022; Su et al, 2022; Zhang et al, 2018). Bartley et al (2006) reported that the presence of vegetation near an outlet had better effects on reducing runoff and sediment loss than bare patches of soil.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations